1993
DOI: 10.1046/j.1365-2648.1993.18081235.x
|View full text |Cite
|
Sign up to set email alerts
|

Young adult women: lifestyle and health locus of control

Abstract: A study of 76 young adult women, 38 nursing students and 38 non-nursing students, examined their lifestyle practices and health locus of control (HLOC). Findings revealed a significant difference between reported lifestyle practices and the career choice of these young adult women. The lifestyle practice areas in which the most notable differences occurred included: use of seat belts, frequency of alcohol use, frequency of junk food intake, use of illegal drugs and hours of sleep per night. While differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…However, a lack of congruence between the MHLC scales and lifestyle practices has been reported (10). For people with a chronic illness who experience episodic, unexplainable symptom fluctuations, an adaptive coping mechanism may be to modify health beliefs toward an external locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of congruence between the MHLC scales and lifestyle practices has been reported (10). For people with a chronic illness who experience episodic, unexplainable symptom fluctuations, an adaptive coping mechanism may be to modify health beliefs toward an external locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…PHLC and/or CHLC are classified as "external" belief, and IHLC as "internal" belief (Wallston and Wallston 1978). In Western countries, the relationships between MHLC score and socio-demographics and various types of health-related behavior such as smoking, drinking, or exercise have been investigated (Slenker et al 1985;Calnan 1989;Fleming and Barry 1991;Schank and Lawrence 1993;Stuart et al 1994;Bennett et al 1997;Paxton and Sculthorpe 1999). Most of the previous studies agreed that people with low socioeconomic status (low income, fewer years of education) or adverse health-related behavior (such as smoking or excess drinking) tend to have higher "external" scores, while people with high socioeconomic status or beneficial health behavior such as regular exercise tend to have higher "internal" scores.…”
mentioning
confidence: 99%
“…T he extent to which an individual perceives life events to be within his or her own control, termed locus of control (LOC), has been examined as a potential correlate of health behaviors (1)(2)(3)(4)(5)(6)(7)(8). Individuals with an external LOC are more likely to believe that life events are determined by chance, other individuals, or other outside factors, but those with an internal LOC believe they have more control over what happens to them.…”
mentioning
confidence: 99%
“…Individuals with an internal LOC may be less likely to smoke (3), more likely to have had a recent pap smear or breast exam (1,8), and less likely to experience a future decline in functional status (9). However, studies have also reported that LOC is not predictive or is only weakly predictive of health behaviors (2,(5)(6)(7).…”
mentioning
confidence: 99%